Mathematical Formulation of River Quality Index Based on Awareness of River Pollution (Contemporary Mathematics, 2025)
A river is an environmental commodity that is essential for the preservation and advancement of a country. Malaysia, however, has witnessed a decrease in the quality of these natural resources since the beginning of time. Therefore, awareness of activities contributing to river pollution is crucial among people, especially those around the riverside. The main purpose of this paper is to develop a mathematical formulation of river quality index based on awareness of river pollution. Thus, this paper identified human activities related to river pollution by interviewing experts and local residents near the riverside in Terengganu and Kelantan. The data collected were analyzed using a thematic analysis procedure in ATLAS.ti. Then, these findings are used to develop a mathematical formulation of a river quality index using basic composite index and human activity parameters found in this study. It is found that eleven activities contribute to negative impact of water river quality: Poor Drainage System, Livestock Farming, Illegal Dumping, Discharge of Untreated Waste, Agricultural Runoff, Attitude, Self-Awareness, Urbanization, Ship Traffic, Sand Mining Activity and Role of Government. Additionally, the weightings for each factor are evaluated and used to develop a mathematical formula based on river pollution awareness. This mathematical formulation can be used as a measurement tool for early detection of pollution sources.
Keywords: awareness; ATLAS.ti; composite index; mathematical formulation; qualitative approach